2017
DOI: 10.1093/heapro/dax082
|View full text |Cite
|
Sign up to set email alerts
|

Occupational health risks and intervention strategies for US taxi drivers

Abstract: Research has shown that taxi drivers are at risk for numerous health concerns, such as low back and leg pain, linked to their highly sedentary occupation, long work hours and stressors related to the job (e.g. low income, safety threats). The goal of this study was to explore occupational health risks and opportunities for health interventions with taxi drivers using community-based participatory research (CBPR) methods. A mixed methods approach included first a convenience sample of 19 East African taxi drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 20 publications
1
44
0
3
Order By: Relevance
“…This may have a plausible qualitative explanation: as it is described in other empirical researches dealing with this specific population, uniform, and scarcely variable outcomes of low skill discretion, decision making, and promotion prospects have been found in this type of jobs; in other words, some studies have shown how professional drivers have, generally, very little influence at work and therefore experience a substantially limited degree of freedom (Chung and Wu, 2013; Gómez et al, 2018). This is summed to other negative issues similarly observed with high frequency in professional drivers, such as job dissatisfaction and insecurity (Murray et al, 2017; Tran and Sokas, 2017), and elevated amounts of physical and psychological demands (Cendales et al, 2016), thus remarking the high psychosocial and environmental vulnerability of the workers who belong to the transport industry. However, and as it has been addressed in this paper, the role of generic scales for assessing the psychosocial work environment of specific occupations remains relatively limited in addressing in-depth particular issues in spheres such as ergonomics, task design and safety outcomes.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…This may have a plausible qualitative explanation: as it is described in other empirical researches dealing with this specific population, uniform, and scarcely variable outcomes of low skill discretion, decision making, and promotion prospects have been found in this type of jobs; in other words, some studies have shown how professional drivers have, generally, very little influence at work and therefore experience a substantially limited degree of freedom (Chung and Wu, 2013; Gómez et al, 2018). This is summed to other negative issues similarly observed with high frequency in professional drivers, such as job dissatisfaction and insecurity (Murray et al, 2017; Tran and Sokas, 2017), and elevated amounts of physical and psychological demands (Cendales et al, 2016), thus remarking the high psychosocial and environmental vulnerability of the workers who belong to the transport industry. However, and as it has been addressed in this paper, the role of generic scales for assessing the psychosocial work environment of specific occupations remains relatively limited in addressing in-depth particular issues in spheres such as ergonomics, task design and safety outcomes.…”
Section: Discussionmentioning
confidence: 69%
“…In short, health outcomes of professional drivers working under highly demanding conditions can be summarized in terms of both physical and mental illnesses, such as: ergonomic complications associated with physical working conditions (Abledu et al, 2014; Jadhav, 2016; Useche et al, 2018), hypertension (Hirata et al, 2012; Djindjić et al, 2013; Platek et al, 2017), respiratory and gastrointestinal disorders (Ekpenyong et al, 2012; Ronchese and Bovenzi, 2012), eye problems (Murray et al, 2017), lung cancer related to the prolonged exposition to contaminant and toxic gasses (Zuskin et al, 1994; Tsoi and Tse, 2012), metabolic syndrome (Lemke et al, 2017; Hege et al, 2019), sleep problems and chronic fatigue (Sabbagh-Ehrlich et al, 2005; Braeckman et al, 2011; Tellez López et al, 2015; Useche et al, 2017; Garbarino et al, 2018), psychological distress and several mental health disturbances such as anxiety, and depressive disorders (Narciso and Mello, 2017; Unsworth et al, 2017; Davidson et al, 2018). Other applied researches, such as the one performed by Taylor and Dorn (2006), Tse et al (2006), Chung and Wong (2011), Useche et al (2018, 2019) and Pérez-Fuentes et al (2019) have related adverse working conditions, workplace stress and burnout of various occupational groups to both adverse psychological health indicators (such as the psychological distress measured by the short form of Goldberg’s GHQ-12) and negative lifestyle outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, more than 60% of taxi drivers report fatigue [ 28 ]. In addition, it is reported that the economic burden of taxi drivers affects their safe driving behavior [ 29 , 30 ], and at least 21% of drivers in fatal accidents reported experiencing sleepiness while driving [ 31 ]. In the case of corporate taxis, they are workers under the Labor Standards Act, and there is no problem when they are involved in occupational accidents because they are workplaces subject to occupational accidents.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is reported that the incidence of cognitive impairment increases with age [ 36 , 37 ], various factors are thought to have an influence on cognitive impairment. In fact, physical and socioeconomic factors are reported to affect traffic accidents and driving behavior, along with cognitive function [ 29 , 30 ]. Therefore, it is thought that the physical health status and socioeconomic burden of taxi drivers indirectly influenced the degree of cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Taxi and for-hire vehicle (FHV) drivers comprise an ethnically diverse workforce facing mounting financial pressures [ 1 , 2 ] and work-related health risks [ 1 , 3 5 ]. Taxi drivers are part of a fast-growing occupational group in the US, which more than doubled from 305,000 in 2016 to 703,000 in 2019 with the increasing popularity of ride-sharing apps, such as Uber and Lyft [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%